Strategic Management Practices and Organizational Performance of Business Process Outsourcing Companies in Nairobi County, Kenya - Ndiritu, Doris; Abel, Anyieni (Integrasi Sains Media, 2025)
The study examines the impact of strategic management practices on the performance of Business Process Outsourcing (BPO) companies in Nairobi County, Kenya. This research was driven by the declining performance and growth of BPOs despite increasing demand for outsourced services from local and international corporations. A descriptive research design targeted 1,257 employees from 118 BPO companies. A sample of 113 respondents was selected using a stratified random sampling technique. Data was collected through a structured questionnaire and analyzed using descriptive and inferential statistics. The findings indicate that strategic leadership, strategic planning, resource mobilization, and strategic culture alignment are crucial in enhancing BPO performance. However, most surveyed firms had not effectively implemented these strategic management practices, leading to suboptimal performance. Among these practices, strategic leadership had the most significant impact, followed by strategic culture alignment, resource mobilization, and strategic planning. From a practical standpoint, the study highlights the critical role of BPOs in economic growth and employment generation. Their underperformance poses a risk to job security and government revenue. To address this challenge, BPO managers should proactively integrate strategic management practices to improve adaptability to external changes and enhance long-term sustainability. This study provides valuable insights for policymakers and business leaders, emphasizing the need for a strong strategic management framework to boost BPO sector performance. Future research could explore additional factors influencing BPO success in emerging economies.